(untitled) (Ustozlar uchun, 2025)
This work analyzes the role of literature during the English Civil War, focusing on the contributions of John Milton and John Bunyan. Milton’s political and philosophical prose defended freedom, republican ideals, and individual conscience, while Bunyan’s allegorical and spiritual writings reflected the Puritan religious experience shaped by the war. The study highlights how their works influenced public opinion, supported ideological struggles, and contributed to the development of English literary and political thought.